Impact of HIV/AIDS in the family on children’s quality of life (Faculty of Medicine Universitas Indonesia, 2010)
Aim: An AIDS epidemic has a negative social and economic impact to the families. The aim of the study is to explore the impact of HIV/AIDS in the family to the quality of life of the children, including other factors that might interfere. Methods: The study utilized the data of a survey conducted by the Health Research Center of the University of Indonesia (2007), in seven provinces consisting of 379 households (HH) with HIV and 370 HH without HIV. Child’s quality of life was measured at ages 5 to 11 years (pre-adolescent) using a composite of three variables (education, social environment, and physical activity), and was scored as ‘poor’ and ‘good’ . Multiple logistic regression was performed to examine the impact of HIV/AIDS, household and child factor towards the child’s quality of life. Results: The presence of an HIV/AIDS patient in the HH increases the risk of poor quality of life 1.59 times comparedto the risk in HH without HIV/AIDS. If the child is a female, the risk of poor quality of life increases 1.50 times compared to male children. A child who is poorly taken care of faces a 1.55 times higher risk of poor quality of life compared to children who are well taken care of. In younger children (5-7 yrs) the risk of poor quality of life increases 1.60 times compared to older children (8-11 yrs). Conclusion: The study showed that when a member of the family is infected with HIV, it will negatively affect the quality of life of a pre-teen child in that family. This negative effect is higher when the child is a female, does not receive proper care, and of younger age. (Med J Indones 2010; 19:280-6) Keywords: child care, children's quality of life, impact of HIV/ AIDS